SURVEY OF PREDATORY MITES INHABITING VEGETABLE CROPS IN KOZHIKODE, KERALA - RAHUL, MP; SADANANDAN, MARY ANITHALATHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
The paper embodies the result of a survey conducted on predatory mite fauna associated with 18 species of vegetable crops belonging to 09 families and 16 genera. The result of the survey yielded 40 species of predatory mites belonging to 19 genera, 05 families of the suborders Mesostigmata, Prostigmata and Astigmata. Of these 04 species belonging to 02 genera are recognized as new to science.